Application of the Think Pair Square Learning Model to Improve Student Chemistry Learning Outcomes in Vocational Schools - Riza Fitri Yanti; Hartono Hartono; Eddy Dharmansyah3 (Pedagogy Review, 2022)
Abstract: Application of Think Application of Think Pair Square Learning Model to Improve Student Chemistry Learning Outcomes in SMK. This research aims to determine the effect of cooperative learning model Think Pair Square (TPS) in improving student’s learning outcomes on colloidal and polymeric subjects in class XI TP 1 SMKN 4 Palembang. The type of research used in this study is a classroom action research conducted two cycles with each stage of the cycle of planning, action, observation dan reflection. The result of student learning test through the model Think Pair Square (TPS) states improvement of first cycle average equal to 63,8 with mastery learning 42,5% and second cycle is 85,33 mastery learning 87,5%. Similarly, the observation of student also increased for the results of student observations on the first cycle is 57,42% and second cycle is 81,40%. Based on Research Results and Discussion can be concluded that there is improvement of learning outcomes of learners from learning outcomes by using cooperative learning model Think Pair Square (TPS) on chemicals in class XI TP 1 SMKN 4 PalembangKeywords: think pair square, classical action, results of student's learning